The Utilization of Coffee Husk Waste as Animal Feed and Organic Fertilizer in Banyuanyar Village, Ampel District, Boyolali Regency. - Rois, Dimas Ilham Nur; Dewi, Riana Rachmawati; Dughita, Putri Awaliya; Sari, Aprilia Dwi Kumala (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this community service is to utilize discarded coffee husk waste into fertilizer and animal feed so that it can be reused by the community in Banyuanyar Village, Ampel District, Boyolali Regency. The method used is training for the Berkah Kopi farmer group to make fertilizer and animal feed in a simple and feasible way by utilizing bacteria and machine technology to simplify the process. The results are organic animal feed and fertilizer that can be used by the community themselves. The recommendation submitted by the PKM team is that animal feed already has high protein especially by utilizing coffee husk so it is safe to use as livestock feed and the fertilizer made is also safe because it is all from livestock and agricultural waste so it is safe to use as fertilizer for coffee plantations.